THE NARRATIVE OF A CHRONIC RENAL FAILURE CLIENT: ORAL HISTORY AS RESEARCH STRATEGY - Luciana Schleder Gonçalves Kobus; Eloísa Zanella; Ana Maria Dyniewicz (Universidade Federal de Goias, 2004)
The objective of this research was to understand the meanings of the failure kidney for a client whofor twelve years is in hemodialisys treatment. The study was developed from November, 2002 through March,2003.The Oral History as a research strategy showed the following categories: The failure kidney sick diagnosticdiscovery and the routine with it; The hemodialisy treatment and its limitation; The concerns about self image; Thehopeness for a kidney transplant; The relationship with health professionals team; The family support; Newprojects of life; Attempts to feel itself useful. The patients narrative showed how difficult is the treatment, dealingchallenges daily, discoveries and hopes, a constant effort to fight against the limits, but demonstrating capacity toexceed the suffering. It was evident the positive and trustful relationship established with the health professionalteam, strengthening its social and ethical commitment in co-responsibility relationship, involvement, cooperation,consensus, dialogue and participative feelings. This study presents how important is to perceive each person as asingular one and the way that this person lives and deals with illness situation.